Ging Jesus über den See Genezareth? - Fischer, Johannes (Evangelische Theologie, 2023)
Did the miracles told about Jesus really happen? And did Jesus really rise from the dead? The author argues that these questions are misleading. The miracles of Jesus and his resurrection are not historical events, but events in the remembered history of Christianity. As such, they are just as real as the latter, which is part oft the lifeworld of Christians.